Empowering the American consumer : corporate responsiveness and market profitability - Samli, A. Coskun (Quorum Books, 2001)
Oligopolistic and indifferent to their markets, companies today are terrorizing the customers they depend on for survival. One result is that the American market system performs far below optimum and farther below its potential. Samli argues that the system must do more than it is doing to encourage competition and create consumer value--things it neglects, he says, because of a mistaken notion that laissez-fairism is working nicely, and that in today's free economy customers and corporations are getting along fine. Not so, says Samli, but by creating true consumer value and stopping their headlong rush to merge, wrongs can be righted and corporations can achieve high, and higher, profit goals. Upper level corporate strategists, marketing executives, and policy makers in government will find Samli's argument challenging and provocative. Academics and their students will consider it an important addition to the literature on how business, government, and society interact. -- Provided by publisher.